Lead isotopes and heavy minerals analyzed as tools to understand the distribution of lead and other potentially toxic elements in soils contaminated by Cu smelting (Legnica, Poland) - Tyszka, Rafał; Pietranik, Anna; Kierczak, Jakub; Ettler, Vojtěch; Mihaljevič, Martin; Medyńska-Juraszek, Agnieszka (Environmental science and pollution research international, 2016)
Surroundings of the Legnica Cu smelter (Poland) offer insight into the behavior of Pb and other metal(oid)s in heavily contaminated soils in a relatively simple site, where lithogenic and anthropogenic Pb contributions have uniform Pb isotope composition over the time of smelter activity. Distribution of metal(oid)s decreases asymptotically with depth and below 30 cm reaches concentrations typical or lower than those of upper continental crust. Usually, such distribution is interpreted as the decrease in anthropogenic Pb contribution with depth. However, calculations based on Pb isotopes indicate that anthropogenic Pb is probably distributed both as Pb-rich particles of slags and fly ashes and Pb-poor soil solutions. Generally, anthropogenic Pb constitutes up to 100 % of Pb in the uppermost 10 cm of the soils and comes often from mechanical mixing with slag and fly ash particles as well as their weathering products. On the other hand, lower soil horizon contains anthropogenic Pb in various forms, and at depths below 30 cm, most of anthropogenic Pb comes from soil solutions and can constitute from 1 to 65 % of the Pb budget. This is consistent with secondary electron microscope (SEM) analyses of heavy mineral particles showing that, in upper horizons, Pb, Cu, and Zn are contained in various particles emitted from the smelter, which show different stages of weathering. Currently, large portion of these metals may reside in the secondary Fe-hydro-oxides. On the other hand, in deeper soil horizons, anthropogenic Pb is probably dominated by Pb coming from leaching of slag or fly ash particles. Overall, metal(oid) mobility is a dynamic process and is controlled by the soil type (cultivated versus forest) and the composition and the structure of the metal-rich particles emitted from the smelter. High proportions of anthropogenic Pb at depths below 30 cm in some soil profiles indicate that Pb (and probably other metal(oid)s) can be transported down the soil profile and the present concentration of anthropogenic Pb depends on the availability of binding sites.
Keywords: olovo; Minerals; Environmental Monitoring; Lead; Copper; izotopy; monitorování životního prostředí; těžké kovy; Poland; látky znečišťující půdu; Soil; Isotopes; Soil Pollutants; hornictví; minerály; měď; Metals, Heavy; půda; Polsko; Mining